2017
DOI: 10.1007/s11292-017-9304-4
|View full text |Cite
|
Sign up to set email alerts
|

Does GPS supervision of intimate partner violence defendants reduce pretrial misconduct? Evidence from a quasi-experimental study

Abstract: Objectives: This research examines the effect GPS supervision has on pretrial misconduct for defendants facing intimate partner violence charges. Methods: Drawing on data from one pretrial services division, a retrospective quasi-experimental design was constructed to examine failure to appear to court, failure to appear to meetings with pretrial services, and rearrest outcomes between defendants ordered to pretrial GPS supervision and a comparison group of defendants ordered to pretrial supervision without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…However, evaluation research in this area confronts similar challenge to PO research where differing systems and concurrent interventions influence outcomes and make comparisons difficult. Some studies have relied solely on administrative data (Grommon, Rydberg, & Carter, 2017), while others have used multiple data sources (Erez et al, 2012; Erez, Ibarra, & Gur, 2013). As technology advances, it is worth consideration of use in combination with PO to increase targeted intervention and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…However, evaluation research in this area confronts similar challenge to PO research where differing systems and concurrent interventions influence outcomes and make comparisons difficult. Some studies have relied solely on administrative data (Grommon, Rydberg, & Carter, 2017), while others have used multiple data sources (Erez et al, 2012; Erez, Ibarra, & Gur, 2013). As technology advances, it is worth consideration of use in combination with PO to increase targeted intervention and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The MMW-S weighting procedure eliminated 16 cases (0.3%). These methods have been shown to be successful in past criminological research (Clark & Rydberg, 2016; Grommon, Rydberg, & Carter, 2017; Rydberg & Clark, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Empirical investigations have considered the effectiveness of GPS or electronic monitoring on pretrial outcomes. Using a sample of individuals arrested for intimate partner violence, Grommon et al (2017) found pretrial GPS supervision was no more effective than traditional pretrial supervision in reducing FTA or rearrest. However, GPS supervision reduced the risk of failure to report to a pretrial supervision officer.…”
Section: Predictors Of Pretrial Failurementioning
confidence: 95%
“…1 Research has investigated the equity of financial factors associated with bail and pretrial supervision (Garrett et al, 2019; Rabuy & Kopf, 2016; Scott-Hayward & Fradella, 2019). Other studies examine many aspects of pretrial supervision, including, but not limited to, the impact of preventive notification before orientation and court dates (Goldkamp & White, 2006); race, ethnicity, and pretrial outcomes (Donnelly & MacDonald, 2018; Fennessy & Huss, 2013; Freiburger & Hilinski, 2010; Menefee, 2018; Zettler & Morris, 2015); the effectiveness of pretrial risk assessments (Cadigan & Lowenkamp, 2011; Cooprider, 2009; DeMichele et al, 2018; Desmarais et al, 2021; Lowenkamp & Whetzel, 2009; Milgram et al, 2014); conditions of release related to failure to appear (FTA; Azari, 2019; Belenko et al, 1992; Siddiqi, 2002); the effectiveness of electronic monitoring (Grommon et al, 2017; Lemke, 2009; Sainju et al, 2018; Wolff et al, 2017); needs and failure (Gehring & Van Voorhis, 2014); and predictors of pretrial failure (Bechtel et al, 2011; Clipper et al, 2021; Siddiqi, 2002). As individuals on pretrial supervision are released back into the community pending their disposition, understanding which factors are associated with failure is of particular concern to pretrial supervision agencies.…”
Section: Literature Reviewmentioning
confidence: 99%